Maven for Eclipse : a fast-paced guide that helps you create a continuous delivery solution by integrating Maven with an Eclipse environment /: a fast-paced guide that helps you create a continuous delivery solution by integrating Maven with an Eclipse environment. (2014) - Shah, Sanjay
No abstract available